Psychometrics of the Functional Oral Intake Scale for Infants - Yi, You Gyoung; Shin, Hyung-Ik (Frontiers in Pediatrics, 2019)
This study aimed to investigate the reliability and validity of the Functional Oral Intake Scale (FOIS) for infants. Infants (age, <1 year) who underwent a videofluoroscopic swallowing study (VFSS) were included in this retrospective study. Their nutrition records at the time of the VFSS were separately evaluated by two raters using the five-point FOIS for infants. Categorical swallowing and aspiration impairment scale data were also obtained from the VFSS. The inter-rater reliability of the FOIS for infants was high (95.5% absolute agreement) among the 201 evaluated infants, and this scale was significantly correlated with aspiration severity in the VFSS. This analysis included 33 infants who were receiving both oral and tube feeding (i.e., partial oral feeding [POF]). Among them, 26 infants achieved full oral feeding without tube feeding after 1 year. Their initial contribution from oral feeding was higher than that in infants who still maintained POF after 1 year (28.46 ± 22.79 vs 6.00 ± 5.45 %, p < 0.001). The five-point FOIS for infants, which reflected the expansion of their oral diet with growth, had adequate reliability and validity. The caloric contribution as well as consistency of oral feeding could be used to distinguish FOIS levels 2 and 3, which correspond to the POF status in infants.